Hinduism and Buddhism a historical sketch - Eliot, Charles Sir 1862-1931. (London Edward Arnold & Co., 1921)
Traces the history and development of religion in India and elsewhere with occasional remarks on its latest phases.
Includes index.
Keywords: Hinduism -- India -- History; Buddhism -- India -- History